2021
DOI: 10.6018/cpd.428691
|View full text |Cite
|
Sign up to set email alerts
|

Relação treinador-atleta e a experiência positiva de jovens no esporte extracurricular

Abstract: La calidad de la relación entrenador-atleta es reconocida como una experiencia positiva por jóvenes deportistas, que puede ser decisiva para la manutención en la práctica. El objetivo de esta investigación fue verificar si la calidad de la relación entrenador-atleta está relacionada con la percepción de la experiencia positiva de los jóvenes en el deporte. El estudio se realizó con 630 atletas (350 mas.; 280 fem.), en los deportes de equipo: balonmano (26%), voleibol (25%), fútbol sala (31%) y baloncesto (18%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Indeed Davis et al (2021) observed that athletes prospered when they realized that the relationship with their coaches was based on affection, confidence, support, and perceived positive expectations about the behavior of coaches and a positive self-image, unlike those athletes who perceived that the relationship with the coach was based on uncertainty and fear of rejection. In addition, the relationship with the coach helps to develop other quality relationships (e.g., family, athletes, opponents) (Holt et al, 2017;Tavares et al, 2021). So, this study corroborates the importance of this relationship in the positive, personal development of athletes.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Indeed Davis et al (2021) observed that athletes prospered when they realized that the relationship with their coaches was based on affection, confidence, support, and perceived positive expectations about the behavior of coaches and a positive self-image, unlike those athletes who perceived that the relationship with the coach was based on uncertainty and fear of rejection. In addition, the relationship with the coach helps to develop other quality relationships (e.g., family, athletes, opponents) (Holt et al, 2017;Tavares et al, 2021). So, this study corroborates the importance of this relationship in the positive, personal development of athletes.…”
Section: Discussionsupporting
confidence: 80%
“…Of these relationships, the athletes establish and sustain with their coach has an important role to play as it is responsible for facilitating the quality of athletes' interpersonal relations, specifically with other athletes, family, institutions, and opponents (Tavares et al, 2021). When these relationships are positive, the coach enables the athletes to experience positive emotions as well as incentivizing greater engagement, satisfaction with practicing the sport and promoting essential aspects for the development of the athlete (Compton, 2005;MacDonald et al, 2010;Tavares et al, 2021;Weiss & Stuntz, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the contextual influence of school deserves consideration. In Brazil, the school context is the main space for access to sports practice, either in the Physical Education class (mandatory curriculum) or in extracurricular activities developed by professionals with a degree in Physical Education (Tavares et al, 2021). This school context represents an important contextual difference in this study compared to other studies in this research domain (Lima et al, 2020; MacDonald et al, 2011; Soares et al, 2020; Zanatta et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The games take place in four phases: a municipal phase – an event among schools in the municipality; a regional phase – an event among champion schools in the municipal phase; the state phase – a competition among regional phase winners at the state level; and a national phase – an event among state schools. In the state of Mato Grosso, located in the central-western region of Brazil, the school games are the main competition in the sporting calendar; they bring together more than 5,000 athletes (Tavares et al, 2021).…”
Section: Methodsmentioning
confidence: 99%